Yellow star, red star : Holocaust remembrance after communism - Subotic, Jelena (Cornell University Press, 2019)
"The book explains how contemporary Holocaust remembrance practices in Eastern Europe are used to deal with various state insecurities, and not remember the Holocaust"--